Tertiary Education in Mongolia : Meeting the Challenges of the Global Economy - World Bank (Washington, DC, 2014)
Since the transition from a planned economy to a market-based democracy in the early 1990s, Mongolian higher education has experienced a marked expansion. Between 1992 and 2007, the number of tertiary education institution (TEIs) has increased more than four-fold and enrollment more than six-fold, with the gross enrollment ratio growing from 14 to 47 percent. This rapid growth has been fueled by the increased demand for higher skills in the labor market and has led to rising education premia. These trends, in turn, have stimulated increased household demand for tertiary education. In the early 1990s, the liberalization of the economy and the legalization of private higher education made it possible to increase the supply of tertiary education. However, this expansion in supply has been met with the charging of tuition fees in public universities and the growth of private institutions. As a result, public expenditure on higher education has been contained to about 14 percent of total expenditure, compared with over 20 percent in China. Although this policy has met the need for an increased supply of tertiary education, it has failed to produce graduates who can improve Mongolia's international competitiveness. The emerging problems are low-cost and low-quality education, a mismatch between the demand for and supply of skills, and inequitable opportunities of access between the urban and rural areas and between the rich and the poor.